Simulation of S-MAC protocol for wireless sensor network - Heng, Wee Meng. (2009)
The availability of low cost hardware has fostered the development of Wireless Sensor Networks and motivated important research issues into the algorithms, protocols and architecture of these ubiquitous wireless networks. The sensor medium access control (S-MAC) is an energy-aware protocol design for wireless sensor network (WSN). WSN is made up of numerous battery-operated sensor nodes deployed in ad-hoc fashion. To complete a given task, such as environmental monitoring, data from individual nodes are transmitted in a store and forward manner, usually requiring multi-hops before reaching the sink. However, these sensor nodes are assumed to remain inactive for long period of time but becoming suddenly active when something is detected. S-MAC was proposed to provide an energy-efficient protocol for both synchronization and data transfers in the network.